Geomorphic evidence for ancestral drainage patterns in the Zagros Simple Folded Zone and growth of the Iranian plateau - Walker, RT; Ramsey, L; Jackson, J (2011)
We describe the geomorphology of a large (∼10000 km2) internally draining region within the Zagros fold-and-thrust belt of Fars province, Iran. A series of wind gaps through fold crests and a continuous line of low-slope pixels in digital elevation models indicate the presence of an older, and now abandoned, through-going river system. We suggest, from the presence of the wind gaps, that the original through-going river system was abandoned as a direct result of fold growth. At present, through-going drainage in Fars is restricted to only two major rivers, the Kul and the Mand, which bound the margins of the internally drained region. The low gradients of the Kul and the Mand rivers are similar to those in topographic profiles drawn along the course of the abandoned drainage. The Mand and Kul rivers may be defeated in the future, causing an expansion of the internally drained region, and resulting in a profound change in the distribution of sediment and surface elevations within the Zagros. The internally draining part of the Zagros resembles the Central Iranian Plateau both in its geomorphology and in the apparently slow rates of deformation within it. We speculate that the development of internally drained basins and distribution of shortening within the range may be causally linked. The geomorphology that we describe might, therefore, record a stage in the southward expansion of the non-deforming and topographically high Central Iranian Plateau. © 2011 Cambridge University Press.